STUDI KRITIS DEKONSTRUKSI SYARI’AH MUHAMMAD AHMED AN-NA’IM - Anwar, Efizal (Institut Darul Quran Payakumbuh, 2016)
Islam is the most perfect religion which is able to solve all problems. Nothing in the world is absent of Qur’an’s watch. The perfectness of the Qur’an can be viewed from Law Verses including universal and fundamental norms. Comprehension of many Islamic experts on the law produces an Islamic law formation called Syariah or fiqh. Syari’ah or fiqh is all of the regulation concerning Allah’s statement relating to the behavior of a mukallaf. The process of forming Islamic law known as syari’ah or fiqh made by Islamic experts in the past which can not be seperated from social life at the time. The condition illustrated above needs a struggle of Islamic greatment to reform Islamic Law, and to set a methodology due to irrelevant to civilization at the present. Therefore, it is very crucial to build a model of syari’ah which is suitable for standardizing, and modern public law dealing with Human Rights, Criminal Law, and International Law.